2014
DOI: 10.1371/journal.pone.0095404
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Clinical Trial of Systemically Delivered NEMO Binding Domain Peptide in Dogs with Spontaneous Activated B-Cell like Diffuse Large B-Cell Lymphoma

Abstract: Activated B-Cell (ABC) Diffuse Large B-Cell Lymphoma (DLBCL) is a common, aggressive and poorly chemoresponsive subtype of DLBCL, characterized by constitutive canonical NF-κB signaling. Inhibition of NF-κB signaling leads to apoptosis of ABC-DLBCL cell lines, suggesting targeted disruption of this pathway may have therapeutic relevance. The selective IKK inhibitor, NEMO Binding Domain (NBD) peptide effectively blocks constitutive NF-κB activity and induces apoptosis in ABC-DLBCL cells in vitro. Here we used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
(64 reference statements)
4
35
0
Order By: Relevance
“…HEK293 cells transfected with a luciferase reporter gene under the control of NF-κB were first treated with varying concentrations of a peptide for 1 h and then TNFα. [9,10e] In the absence of any inhibitory peptide, treatment with 5 ng/mL TNFα increased the luciferase activity from a basal level of 177 arbitrary units (AU) to 715 AU (data not shown). Peptide 4 reduced the TNFα-induced luciferase activity in a dose-dependent manner, with an IC 50 value of ~20 μM (Figure 1c).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…HEK293 cells transfected with a luciferase reporter gene under the control of NF-κB were first treated with varying concentrations of a peptide for 1 h and then TNFα. [9,10e] In the absence of any inhibitory peptide, treatment with 5 ng/mL TNFα increased the luciferase activity from a basal level of 177 arbitrary units (AU) to 715 AU (data not shown). Peptide 4 reduced the TNFα-induced luciferase activity in a dose-dependent manner, with an IC 50 value of ~20 μM (Figure 1c).…”
mentioning
confidence: 98%
“…[9] In several pre-clinical studies, Antp-NBD demonstrated in vivo efficacy for treating Duchenne muscular dystrophy and large B-cell lymphoma in mouse and canine models. [10] However, to achieve clinical utility, Antp-NBD would benefit significantly from improvements in its NEMO-binding affinity, metabolic stability, and cell-permeability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate phase 1 clinical trial, these same investigators showed that NBD peptide administered intravenously is safe and effective at inhibiting constitutive NF-κB activity in a subset of dogs with lymphoma (85).…”
Section: Comparative Oncology: An Opportunity To Accelerate Parallel mentioning
confidence: 98%
“…33 Antp-NBD has been used as an NF- κ B inhibitor in numerous in vitro and in vivo studies. For example, it has demonstrated in vivo efficacy for treatment of acute lung injury, 34 Duchenne muscular dystrophy, 35,36 and large B-cell lymphoma 37 in murine and canine models. However, its low potency and poor pharmacokinetics (e.g., serum half-life of ~15 min) prevented further clinical development.…”
Section: Introductionmentioning
confidence: 99%